FENOMENA KAWIN KONTRAK DALAM PERSPEKTIF GENDER DI KABUPATEN JEPARA - Nawati, Ayun (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
This study aims to determine the effects of the implementation of contract marriages on rented wives in Jepara Regency, and analyze the forms of gender injustice that occur in contract marriages in Jepara Regency. This study used a qualitative approach with the research subject being rented wives, namely women who were married to contracts with foreign nationals. The data collection techniques use the method of observation, interviews and documentation. Data validity uses triangulation techniques, and data analysis is done by steps: data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that contract marriage in Jepara Regency is carried out in privacy and in disguise. Perpetrators use religious guise to fool the public by means of married siri, but there are also those who are officially married. The impact caused to the wife of the contract in the form of sociological, psychological and economic impacts both positive and negative. Gender injustice experienced by contract wives in the form of violence, double burden, and negative stereotypes in the community.Keyword:Marriage contract,Gender perspective,Jepara